2020
DOI: 10.1155/2020/5657864
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Relationship of GDF-15 with Clinical Characteristics, Cardinal Features, and Survival in Multiple Myeloma

Abstract: Growth differentiation factor 15 (GDF-15), a member of the transforming growth factor-β superfamily, participates in processes associated with myeloma development and its end-organ complications. It plays a significant role in both physiological and abnormal erythropoiesis and regulates iron homeostasis through modulation of hepcidin. It is abnormally secreted in marrow stromal cells of patients with multiple myeloma (MM), which may reflect the tumor microenvironment. We analyzed the associations of serum GDF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…MM is a malignant condition that manifests with bone disease, renal failure, and anemia. It has been demonstrated that the serum concentration of GDF15 in patients with MM is positively correlated with the established prognostic factors of the disease, and that these concentrations were significantly higher in the studied patients with anemia and inversely correlated with blood hemoglobin and serum iron [64]. A recent report showed that the levels of GDF15 mRNA were increased during erastin-induced ferroptosis.…”
Section: Gdf15 Iron Metabolism and Covid-19mentioning
confidence: 91%
“…MM is a malignant condition that manifests with bone disease, renal failure, and anemia. It has been demonstrated that the serum concentration of GDF15 in patients with MM is positively correlated with the established prognostic factors of the disease, and that these concentrations were significantly higher in the studied patients with anemia and inversely correlated with blood hemoglobin and serum iron [64]. A recent report showed that the levels of GDF15 mRNA were increased during erastin-induced ferroptosis.…”
Section: Gdf15 Iron Metabolism and Covid-19mentioning
confidence: 91%
“…These changes were observed at 2nd week of treatment, preceding the development of anemia (at the 4th to 12th week). Correlation of high level of GDF-15 with low hemoglobin level had been reported in patients with anemia of chronic disease, ineffective erythropoiesis, multiple myeloma, heart failure and chronic kidney disease [Theurl, 2010 #63][Tanno, 2010 #64][Banaszkiewicz, 2020 #65][Przybyłowski, 2014 #66][Ueland, 2021 #67][Nalado, 2020 #68] [18] , [19] , [20] , [21] , [22] , [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Also, VCAM-1 and α4β1 integrin not only enhance adherence of MM to BMSCs but also induce IL-6 and RANKL expression by BMSCs, stimulating OCs formation [4,23]. Then, serum-increased levels of GDF-15 are associated with more advanced MM stages [77]. The interaction of OBs and myeloma cells can produce TGF-β to suppress the self-differentiation of OBs [53].…”
Section: Drugs Targeting Tgf-β and Future Perspectivesmentioning
confidence: 99%